Studi tentang Pengaruh Self-efficacy, Persepsi atas Lingkungan, dan Perhatian Orang Tua terhadap Hasil Belajar Numerasi Siswa Kelas XII di SMA XYZ [A Study on the Influence of Self-Efficacy, Perception of the Environment, and Parental Attention on the Numeracy Learning Outcomes of Grade XII Students at XYZ High School] - Fajar Addana; Taryo; Taufik Hidayat (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2025)
One of the most crucial components of education is numeracy, which helps pupils comprehend arithmetic, reason logically, and make prompt, accurate judgements. This study aims to investigate the simultaneous impact of parental attention, environmental perception, and self- efficacy on students' numeracy learning results. This quantitative study uses the population of SMA XYZ 12th graders for the 2023–2024 school year, and employs a straightforward random selection procedure to select a sample of ninety students. We used a non-test questionnaire with a Likert scale as the study tool, and conducted descriptive, prerequisite, and hypothesis analyses to examine the data. According to the research findings, self- efficacy, parental attention, and environmental perception all significantly impact children's numeracy learning outcomes at the same time, accounting for 65% of the total. Other factors not covered in this study account for the remaining 35%. Self-efficacy, which confirms that students' self-confidence in their academic ability is the primary element driving learning achievement, has a considerable impact on numeracy learning outcomes. However, there is no discernible partial impact of parental attention or environmental perception on learning outcomes related to numeracy. These results highlight how crucial it is to boost students' self-efficacy through encouraging and motivating teaching methods in order to enhance their learning outcomes in numeracy. Parents and teachers can use these results as a guide to promote improved numeracy performance.